2018
DOI: 10.1111/aos.13885
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between handheld digital device use and asthenopia in Chinese college students: a Shanghai study

Abstract: Purpose: The purpose of this study was to investigate the use of handheld digital devices and the prevalence of self-reported asthenopia among college students in China and their potential relationship. Methods: Five thousand students were randomly assessed using a self-reported asthenopia questionnaire. The students' demographic characteristics and habits regarding digital device use were recorded. Univariate analysis was performed to select potential risk factors, and multivariate logistic regression was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 20 publications
2
24
1
4
Order By: Relevance
“…In another study, the prevalence of asthenopia was found to be 53.3% in collage students. Also workload, time spent on computer per day, sexuality and time spent on handheld digital devices were found sinificantly related eye fatigue/astenopia in this study (Xu, Deng, Wang, Xiong & Xu, 2019). All social layers in society have been seriously affected by the Covid-19 pandemic.…”
Section: Introductionsupporting
confidence: 47%
“…In another study, the prevalence of asthenopia was found to be 53.3% in collage students. Also workload, time spent on computer per day, sexuality and time spent on handheld digital devices were found sinificantly related eye fatigue/astenopia in this study (Xu, Deng, Wang, Xiong & Xu, 2019). All social layers in society have been seriously affected by the Covid-19 pandemic.…”
Section: Introductionsupporting
confidence: 47%
“…In the study in Iran which adopted the same definition of asthenopia as ours, the prevalence of asthenopia was 49.4 %. [ 5 ] High prevalence of asthenopia was also found among many college students in various countries: China 53.5%,[ 6 ] Malaysia 89.9%,[ 7 ] Egypt 86%,[ 8 ] and very recently in Iran 70.9%. [ 9 ]…”
Section: Discussionmentioning
confidence: 99%
“…17 Duration of digital screen time was shown be significantly associated in several studies. 9,10,13,19,21,29,30 Better ergonomic practices' knowledge and practicing the preventive measures is significantly associated with DES symptoms as shown in studies done by Ranasinghe et al, Agarwal et al and Shantakumari et al 11,14,18 Contact lens wearers are more likely to suffer DES than non-lens wearers according to Tauste et al 31 Critical fusion frequency decreased significantly after visual task according to Lin et al who studied the effects reflected glare and visual field lighting. 32…”
Section: Factors Associated With Desmentioning
confidence: 98%
“…In the present study, 89.5% students stated experiencing the symptoms of DES which is similar to that reported by Logaraj et al and Reddy et al 9,10 The prevalence of DES or CVS ranged from 53-73% in several other studies on computer users. [11][12][13][14][15][16][17] In a study in Malaysia conducted on 795 university students aged between 18 and 25 years, 89.9% of students surveyed feeling any type of symptom of DES. 10…”
Section: Prevalencementioning
confidence: 99%